PENGARUH SETTING PERON TERHADAP ADAPTABILITAS PENGGUNA KRL STUDI KASUS: STASIUN KERETA API KEBAYORAN PADA JAM SIBUK - Muhammar Khamdevi (NALARs, 2015)
ABSTRACT. The increasing population of Jakarta caused huge number of passengers of Commuter Line (KRL), especially during rush hour . For instance, Serpong Line (Serpong - Manggarai). The trip Frequency of Serpong Line has been no additions yet, though the number of passengers continues to increase. Kebayoran station has a very short platform, that made the passengers in difficult conditions (Dira, 2011) . The Limited wide of the platform and low platform type must bring difficulties. To go up and down the train, the passengers should use "bancik", which is a small staircase made of iron. But now, long iron staircases has been built along the side of the platform, which is also used by the passengers as a seat. But it made the wide of the platform smaller and narrow. In addition, the number of passengers caused the platform becomes congested that will cause discomfort and the passengers will begin to adapt to these conditions. Is there a relationship between the platform setting to the passenggers adaptability? Is there any influence of the platform setting to the passengers adaptability? This study has used quantitative methods to determine the presence or absence of the influence by using SPSS  software version 16. Through this research is expected to provide knowledge on the influence of the platform setting to the passengers adaptability. The results of this study showed that there was indeed a strong and significant correlation, with r = 0.553 and t = 4.59, between the platform setting to the passengers adaptability. And the influence of the platform setting to the passengers adaptability are around 30,5% ABSTRAK. Bertambahnya penduduk kota Jakarta menyebabkan terjadinya lonjakan penumpang Commuter Line (KRL), terutama pada jam sibuk. Salah satunya adalah Serpong Line (Serpong-Manggarai). Frekuensi perjalanan KRL Serpong Line hingga kini belum ada penambahan, padahal jumlah penumpang terus mengalami peningkatan. Peron di Stasiun Kebayoran Lama sangat pendek sehingga menyulitkan penumpang (Dira, 2011). Luas peron yang terbatas tersebut dan ditambah dengan jenis peron yang rendah pasti sangat menyulitkan. Untuk naik-turun, penumpang harus  menggunakan bancik, yaitu tangga kecil yang terbuat dari besi. Namun sekarang sudah dibangun tangga besi sepanjang sisi peron, yang justru digunakan sebagai tempat duduk, namun di lain sisi justru makin mempersempit luas peron. Selain itu banyaknya penumpang menyebabkan peron menjadi sesak yang akan menimbulkan ketidak nyamanan dan mulai beradaptasi terhadap kondisi tersebut. Adakah hubungan antara setting peron dengan adaptabilitas KRL? Adakah pengaruh setting peron terhadap adaptabilitas pengguna KRL? Penelitian ini menggunakan metode kuantitatif untuk mengetahui bahwa ada atau tidaknya pengaruh tersebut dengan menggunakan software SPSS versi 16. Melalui penelitian ini diharapkan dapat memberi pengetahuan mengenai pengaruh setting peron terhadap adaptabilitas pengguna KRL. Hasil penelitian ini menunjukkan bahwa ternyata memang ada hubungan yang kuat dan signifikan dengan r=0,553 dan t=4,59 antara setting peron terhadap adaptabilitas pengguna KRL. Dan pengaruh setting peron terhadap adaptabilitas pengguna KRL sebesar 30,5 %.